PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PERKULIAHAN EVALUASI PEMBELAJARAN MAHASISWA PENDIDIKAN EKONOMI FKIP UNIVERSITAS RIAU - Sumarno ' (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2013)
This study aims to increase learning motivation and outputstudent of Economic Education FKIP Riau University through contextual teaching learning. This study is Classroom Action Research (CAR) in the Evaluation of Teaching Learning Economics course of the school year 2011/2012, which was as much as two cycles. Number of students in this class there are 41 people consisting of four men and 37 women. The results showed that the activity of lecturers on the course with contextual teaching learning model becomes more comprehensive, that there are only four activity to be 10 activity. In cycle 1 activity lecturer achieve enough good category, while in cycle 2 increased to good category.. Student motivation to learn before the implementation of the action is low, while in cycle 1 had increased into enough categories and in cycle 2 increase in the high category leads to very high. Knowledge and skills learning output of students before the implementation of the action only in the category is quite low, in cycle 1 had increased, although still quite enough, and in cycle 2 increased to good category leads very well. Increasing from prior cycle to cycle 1 and from cycle 1 to cycle 2, indicating a significant improvement on the significance level of 0.000. Keywords: teaching learningevaluation, contextual teaching learning, motivation to learn, learning output.